1975
DOI: 10.1007/bf00410035
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic study on the blood-optic nerve and fluid-optic nerve barrier

Abstract: Utilizing horseradish peroxidase as a tracer, electron microscopic studies were done on the blood-optic nerve and fluid-optic nerve barrier to the peroxidase diffusion. Following intravenous injection the peroxidase was observed to fill the lumen of the capillaries of the laminar, prelaminar and orbital portions of the optic nerve but there was no penetratation of the capillary walls. The obstruction of the tracer diffusion out of capillary walls was attributed to the tight junctions between the endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…horseradish peroxidase and lanthanum nitrate) from the choroid into the optic nerve was observed, whereas the penetration of these tracers from the optic nerve into the retina was hardly seen [45][46] .…”
Section: Imt (Intermediary Tissue At the Termination Of The Retina [Kmentioning
confidence: 97%
“…horseradish peroxidase and lanthanum nitrate) from the choroid into the optic nerve was observed, whereas the penetration of these tracers from the optic nerve into the retina was hardly seen [45][46] .…”
Section: Imt (Intermediary Tissue At the Termination Of The Retina [Kmentioning
confidence: 97%
“…These findings build on early work in which tracers injected into the CSF were noted in the optic nerve. [10][11][12] Previously, diaminoacridine dyes 11 (469 Da), sodium fluorescein 10 (376 Da), or horseradish peroxidase 12 (44 kDa) were injected into CSF and found diffusely throughout the optic nerve. These studies were conducted in rabbit, 11 cat, 11 dog, 11 guinea pig, 11 rhesus monkey, 10,11 and mouse.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In the brain, a glymphatic pathway has been described in which CSF flows into and out of the parenchyma along spaces formed between blood vessels and an ensheathing layer of astrocytic endfeet. 13,14 The glymphatic pathway consists of paravascular inflow of CSF into brain parenchyma and clearance of fluid and extracellular solutes from the interstitium.…”
mentioning
confidence: 99%
“…For example, Rodriguez-Peralta (1963) injected diaminoacridine dye into the cisterna magna of rabbits, cats, guinea pigs, and rhesus monkeys and, after one hour, observed a high con centration of the dye in the subarachnoid space of the optic nerve as well as diffusion into the optic nerve, and optic nerve head, including the intermediary tissue of Kuhnt. Similar observations were made by Tsukahara and Yamashita (1975) when they injected horseradish peroxidase in the lateral ventricles of the mice. This free passage and diffusion of cere brospinal fluid from the intracranial subarachnoid to the orbital part may have some influence on the optic nerve pressure up to the area behind the area cribrosa of the sclera, a factor which Hayreh (1978) claimed to play a role in the pathogenesis of edema of the optic nerve head in pri mates.…”
Section: Introductionsupporting
confidence: 79%
“…In addition, Schaltenbrand and Putnam (1927) reported that the meninges of the central nervous system are freely permeable, which has been confirmed by Brightman and Reese (1969) and Waggenner (1964). Further, the free passages of materials from the cerebrospinal fluid into the optic nerve sheath, optic nerve, and optic nerve head up to the intermediary tissue of Kuhnt were demonstrated by Rodriguez-Peralta (1963) in rabbits, cats, guinea pigs, and rhesus monkeys; Grayson and Laties (1971) in rats, and Tsukahara and Yamashita (1975) by Krabill (1979) in the sheep during bypass breathing. This also con forms with the findings of Hayreh (1964) (Krabill, 1979) might be responsible for the disc ele vation and its persistence after three days of normal breathing (which will presumably lower the cerebrospinal fluid pressure).…”
Section: Discussionmentioning
confidence: 96%